Lung transplantation for idiopathic pulmonary arterial hypertension: perioperational features - V. N. Poptsov; E. A. Spirina; I. V. Pashkov; A. V. Belikova; D. O. Oleshkevich; R. A. Latipov; O. M. Tsirulnikova; A. C. Epremian; E. F. Shigaev; S. V. Gautier (Вестник трансплантологии и искусственных органов)
Lung transplantation (LT) for idiopathic pulmonary arterial hypertension (IPAH) now is the only radical treatment of this disease.Aim: to analyze own experience of performing LT in patients with IPAH.Materials and methods. 8 adult IPAH patients, who underwent LT between 2014 and october 2018, were included. In 7 of 8 patients undergoing bilateral lung transplantation on intraoperative venoarterial extracorporeal membrane oxygenation (VA ECMO) with prolongation into the postoperative period.Results. VA ECMO support was prolonged into postoperative period 6 and 7 days respectively in 2 (25,0%) patients and 3 days in 6 (75,0%) patients. Hospital mortality in IPAH patients was 1.Conclusions. Own experience demonstrates that LT is an effective method of treatment in patients with IPAH. Hospital, 1- and 3-year survival rates for the patient collective were 87.5, 75.0 and 75.0% respectively.